Associations between school liking, loneliness and social relations among adolescents: Northern Finland Birth Cohort 1986 study. Issue 1 (2nd January 2017) - Rönkä, Anna Reetta; Sunnari, Vappu; Rautio, Arja; Koiranen, Markku; Taanila, Anja
Abstract: School is an important social environment, but it can also be a devastating place for those who experience loneliness, are bullied or have problematic social relations. These negative experiences might be associated with school dislike, which in turn can negatively affect pupil's motivation, academic success and overall well-being. This study examined the associations between school liking with self-reports of experiences of loneliness and social relations in the Northern Finland Birth Cohort 1986. The answers of 16-year-olds to two adolescents' questionnaires were investigated ( n  = 5817) using binomial logistic regression. For girls, variables associated with school dislike were being somewhat or very lonely, for girls and boys hanging around with friends/kids who get in trouble and for boys being afraid of going to school and not getting along with other adolescents. Schools should pay attention to creating safe and supporting social and learning environment so that everyone can thrive at school.